2023
DOI: 10.3390/su15043510
|View full text |Cite
|
Sign up to set email alerts
|

A Nuanced Analysis on Livelihood Resilience of Vietnamese Upland Households: An Intersectional Lens of Ethnicity and Gender

Abstract: “How to gauge the resilience of a household’s livelihood?” and “who is resilience for?”; as the world’s volatility increases, especially with unprecedented changes in climate, interest in these questions continues to rise. While many previous conventional attempts to measure resilience at the household level have largely employed the “objective” top-down framework relying mostly on a macro observed socioeconomic dataset, this present work seeks to estimate household resilience through an alternative bottom-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…showed that flood damage variables significantly impact rice households' vulnerability in Nghe An Province, Vietnam. Similarly, Phuong et al (2023) found that household vulnerability was positively correlated with extreme weather events and disaster damage. Hilemelekot et al (2021), in turn, claimed that Ethiopian farmers, who are frequently exposed to floods, are forced to implement a range of adaptation strategies.…”
Section: Figure 1 -Conceptual Framework Of the Studymentioning
confidence: 95%
See 3 more Smart Citations
“…showed that flood damage variables significantly impact rice households' vulnerability in Nghe An Province, Vietnam. Similarly, Phuong et al (2023) found that household vulnerability was positively correlated with extreme weather events and disaster damage. Hilemelekot et al (2021), in turn, claimed that Ethiopian farmers, who are frequently exposed to floods, are forced to implement a range of adaptation strategies.…”
Section: Figure 1 -Conceptual Framework Of the Studymentioning
confidence: 95%
“…In addition, flood knowledge and awareness, recommended by Phuong et al (2023), were added as subcomponents by comparing and Hahn et al (2009). Furthermore, knowledge and awareness of flood risks through participation in training or disaster preparedness drills have been found to enhance household adaptivity (Ha et al, 2022;Phuong et al, 2022;Vo et al, 2021), which in turn reduces vulnerability.…”
Section: Determinants Of Flood Vulnerabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Central Vietnam is considered one of the most hazard-prone regions to climate variability, especially typhoons and floods due to its long coastline, hot and humid climate conditions, and geographical disadvantage [ 3 , 8 , 48 , 49 ]. In the study, the field surveys were specifically conducted in two mountain communes – Song Kon (SK), Dong Giang district; and Tra Doc (TD), Bac Tra My district, Quang Nam Province, Central Vietnam ( Fig.…”
Section: Methodsmentioning
confidence: 99%